Pengaruh Corporate Governance terhadap Penghindaran Pajak (Studi Empiris pada Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Jati, Febrilia Retno Sekar; Norviana, Syahida; Jannah, Lu'lu'ul (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to examine the effect of corporate governance on tax avoidance. The low tax ratio in Indonesia is factor caused the practice of tax avoidance. Population.in.this study is all healthcare sector companies listed. on the IDX 2018–2022 period. The sample selection results using the purposive sampling method. The data analysis technique using multiple linear regression tests with SPSS 26. The results in this study show that family ownership has a negative significant effect on tax avoidance. Managerial ownership and board of directors has a positive significant effect on tax avoidance. Independent board of commissioners has a negative but not significant effect on tax avoidance. Audit committee and audit quality has a positive but not significant effect on tax avoidance. This study has the implication that family ownership can reduce tax avoidance, because companies with family ownership will maintain the company reputation in the future.